Effects of Subanesthetic Ketamine Administration on Visual and Auditory Event-Related Potentials (ERP) in Humans: A Systematic Review - Schwertner, André; Zortea, Maxciel; Torres, Felipe V.; Caumo, Wolnei (Frontiers in Behavioral Neuroscience, 2018)
Ketamine is a noncompetitive N-Methyl-D-Aspartate (NMDA) receptor antagonist whose effect in subanesthetic doses has been studied for chronic pain and mood disorders treatment. It has been proposed that ketamine could change the perception of nociceptive stimuli by modulating the cortical connectivity and altering the top-down mechanisms that control conscious pain perception. As this is a strictly central effect, it would be relevant to provide fresh insight into ketamine's effect on cortical response to external stimuli. Event-related potentials (ERPs) reflect the combined synchronic activity of postsynaptic potentials of a large number of cortical pyramidal neurons similarly oriented, being a well-established technique to study cortical responses to sensory input. Therefore, the aim of this study was to examine the current evidence of subanesthetic ketamine doses on patterns of cortical activity based on ERPs in healthy subjects. To answer the question whether ERPs could be potential markers of the cortical effects of ketamine, we conducted a systematic review of ketamine's effect on ERPs after single and repeated doses. We have searched PubMed, EMBASE and Cochrane Databases and pre-selected 141 articles, eighteen of which met the inclusion criteria. Our findings suggest that after ketamine administration some ERP parameters are reduced (reduced N2, P2, and P3 amplitudes, PN and MMN) while others remain stable or are even increased (P50 reduction, PPI, P1 and N1 amplitudes). The current understanding of these effects is that ketamine alters the perceived contrast between distinct visual and auditory stimuli. The analgesic effect of ketamine might also be influenced by a decreased affective discrimination of sensorial information, a finding from studies using ketamine as a model for schizophrenia, but that can give an important hint not only for the treatment of mood disorders, but also to treat pain and ketamine abuse.